Feelings about Nursing Assistants that Enhance the Work Motivation of Japanese Registered Nurses and Licensed Practical Nurses - Yasushi KUDO; Keiko KONO; Ryuko KUME; Ayako MATSUHASHI; Akizumi TSUTSUMI (Journal of UOEH, 2017)
[Abstract]: Registered nurses and licensed practical nurses have received professional education, but to enhance their work motivation it is necessary to create work environments in which they can concentrate on their jobs as specialists. One of the methods to develop such work environments is to use nursing assistants effectively. We investigated professional nurses' feelings toward nursing assistants and then examined the associations between those feelings and their work motivation. The analyzed subjects were 2,170 female nurses working in 25 hospitals with from 55 to 458 beds. The average age of the respondents was 38.0 (standard deviation, 10.6 years). Factor analyses extracted four factors of professional nurses' feelings toward nursing assistants: 1. knowledge related to healthcare, 2. nursing assistants' attitudes toward work, 3. human relations, and 4. distinguishing between professional nurses' work and nursing assistants' work. Using multiple linear regression analysis, our results revealed that scores of maintaining a high motivation to work thanks to nursing assistants became lower as the ages of the respondents increased. Scores of maintaining a high motivation to work thanks to nursing assistants became higher as professional nurses gained satisfaction from: knowledge related to healthcare, nursing assistants' attitudes toward work, and human relations. Hospital managers should consider these findings to improve working environments in which professional nurses can feel motivated to work.